Use of Contraceptive Methods among Young Married Women in Nepal - Lamichhane, Kamala Devi (Tribhuvan University Journal, 2018)
Nepal has a fairly high adolescent fertility rate and low use of contraception. Lack of contraceptive use is a major contributor to the high rates of unintended pregnancies amongst youth. There is also lack of specific studies dealing with contraceptive behavior among young married women. This study examines the use and determinants of contraceptive methods over the time period of 15 years (2001-2016) among young women in Nepal. Trend and bi-vatiate analysis of this study is based on the Nepal Demographic and Health Survey (NDHS), 2001, 2006, 2011 and 2016 data. The multivariate analysis is based on NDHS 2016 data of 2059 currently married non-pregnant young women aged 15-24 years. Logistic regression is used to assess the net effect of independent variables on dependent variable. The study shows that the contraceptive prevalence rate of young women is only 34 percent. Number of living children, spousal separation, husband education, women, occupation, wealth status, caste/ethnic affiliation, fertility preference, decision making status, ideal number of children they prefer and media exposure, are statistically associated to the use of contraception among young women in Nepal. There is a need to strengthen income generating activities so as to improve young women's socio-economic status which will translate into female economic and social empowerment hence ability to discuss sexuality related issues. Family planning programmes should be designed so as to address the contraceptive need of young women especially the low parity and Muslim adolescents.